Flächenutzung! - Ruppert, Karl (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
The article explains the land use in context of whole social aspects. Contemporary modell could be understood as an interim stage of spatial processes and as a consequence of different human activities; acordingly as hing between society and environment. The author underlines the consequence of public taxable measures and warns, that the object-oriented land use policy must be considered instead of multi-layer diferentiation of spatial structures.
Keywords: kulturna pokrajina; prostorski razvoj; raba prostora; raba tal; spremembe